A Double Regime in the Malabar Church (1663-1716) - Mundadan, A M (Journal of Dharma, 1983)
Thomas Pallipurathkunnel A Double Regime in the Malabar Church (1663-1716) Alwaye: Pontifical Institute of Theology and Philosophy, 1982, xi + 183 pp.